ISLAMIC EDUCATION PERSPECTIVE IMAM AL-GHAZALI AND ITS RELEVANCE WITH EDUCATION IN INDONESIA - Aset Sugiana (JURNAL TARBIYAH, 2019)
This study aims to describe Islamic education according to Imam al-Ghazali and its relevance to education in Indonesia. The method of this research was to use library research. The research data was obtained from the results of the recording of Imam al-Ghazali's thoughts about Islamic education, and education in Indonesia. The validity of data was discussed and consulted from data findings to experts and peers. The results of this study are 1) The principle of the importance of morality integrated in spirituality in the goals of character education in accordance with the Republic of Indonesia Law Number 20 of 2003, 2) The values of Islamic education in al-Ghazali's perspective in Indonesia were characterized by Islamic nuances (Integrated Islamic Schools), 3) Educational methods by paying attention to differences in students and according to their education level, 4) The objectives of al-Ghazali's curriculum bring goodness, both in the world and the hereafter, as stated in the Republic of Indonesia Law Number 20 of 2003 concerning Chapter X Article 36 Paragraph 1 and 3.